2015
DOI: 10.3892/ijmm.2015.2076
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 regulates triglyceride and cholesterol metabolism in non-alcoholic fatty liver disease by targeting HMGCR

Abstract: Non-alcoholic fatty liver disease (NAFLD) has emerged as a public health issue with a prevalence of 15-30% in Western populations and 6-25% in Asian populations. Certain studies have revealed the alteration of microRNA (miRNA or miR) profiles in NAFLD and it has been suggested that miR-21 is associated with NAFLD. In the present study, we measured the serum levels of miR-21 in patients with NAFLD and also performed in vitro experiments using a cellular model of NAFLD to further investigate the effects of miR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 27 publications
4
79
0
3
Order By: Relevance
“…Thus, one possible explanation for the increased HMGCR expression in Dicer1-KO mouse livers may be due to some miRNAs deficiency, which prevented the targeting of HMGCR. Recent studies have shown that some miRNAs can downregulate the expression of HMGCR directly or indirectly [24,26,[46][47][48] . For example, miR-21 can regulate cholesterol metabolism by targeting HMGCR directly in vitro [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possible explanation for the increased HMGCR expression in Dicer1-KO mouse livers may be due to some miRNAs deficiency, which prevented the targeting of HMGCR. Recent studies have shown that some miRNAs can downregulate the expression of HMGCR directly or indirectly [24,26,[46][47][48] . For example, miR-21 can regulate cholesterol metabolism by targeting HMGCR directly in vitro [46] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ChREBP might activate the expression of miR species that specifically target cholesterol metabolism. Several liver-rich miRs, including miR-21 (42,43), miR-33 (44), and miR34a (16), have been shown to suppress HMGCR expression. Our microarray data showed that several miR species were selectively downregulated in HFrD-fed Chrebp -/-mouse livers.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, up-regulation of miR-125b by estrogen protects against NAFLD in female mice [13]. MiR-21 decreases the levels of triglyceride and cholesterol by targeting HMGCR [14]. Thus, these studies have raised the enthusiasm to explore the roles of miRNAs in NAFLD.…”
Section: Introductionmentioning
confidence: 99%